PEMANFAATAN KOLEKSI REFERENSI (ENSIKLOPEDIA) DALAM MEMENUHI KEBUTUHAN INFORMASI SISWA SMAN 13 PADANG - Yelli Kurnia Illahi; Marlini Marlini (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This study aims to find out how to use reference collections (encyclopedias) for class XI IPA2 students of SMAN 13 Padang regarding science students and how to fulfill the information needs of class XI IPA2 students in science subjects to the availability of reference collections (encyclopedias) in the library of SMAN 13 Padang. This research is a quantitative research with a descriptive approach. To obtain data in this study, namely by distributing questionnaires to respondents, namely class XI IPA2. Data analysis techniques are carried out by means of verifying the data obtained, tabulating the results of questionnaires, analyzing in a description of the data obtained and drawing conclusions. The result of this study is that class XI IPA2 students make good use of reference collections (encyclopedias) regarding science lessons and the fulfillment of the information needs of class XI IPA2 students regarding science lessons is also relatively good.